Revalidation of Phalangomyia Dyar & Knab as a subgenus of Culex L. (Diptera: Culicidae) based on morphological and molecular evidence - González, Christian R.; Reyes-Valenzuela, Carolina; Rossi, Gustavo C.; Laurito, Magdalena (Zootaxa, 2023)
Culex apicinus Philippi, 1865 and its synonyms, Phalangomyia debilis Dyar & Knab, 1914, Cx. escomeli Brèthes, 1920 and Cx. alticola Martini, 1931, were re-examined employing molecular and morphological phylogenetic methods. Archival and fresh specimens were used for morphological diagnosis and to generate fragments of two single-copy nuclear genes (CAD, HB) and one mitochondrial gene (COI). Additional sequences of Cx. apicinus and species of the subgenus Culex of Culex Linnaeus, 1758 and other subgenera of the genus were obtained from GenBank for molecular analysis. Diagnostic morphological characteristics of Cx. apicinus and other species of the subgenus Culex were contrasted. Phylogenetic relationships were generated using DNA sequences of protein coding genes under both Maximum Likelihood and Bayesian approaches. Culex apicinus showed unique morphological traits that allow its classification in a separate subgenus. The subspecific status is supported by its recovery as a monophyletic clade within the genus Culex based on morphological and molecular characters. The synonymous Phalangomyia debilis provides an available subgeneric name. Consequently, Phalangomyia Dyar & Knab, 1914 is resurrected from synonymy with Culex Linnaeus, 1758 as a monobasic subgenus of Culex.